Laser land leveling: A sustainable approach towards resource conservation technology - Sahu, Raghubar; Kumar, Devesh; Sohane, R K; Kumar, Rakesh (Indian Farming, 2023)
Laser Land leveling (LLL) is a methodology of leveling land surface (±2 cm) from its average elevation utilizing laser machine equipped drag buckets to achieve precision in land leveling. With precision land leveling, fields are modified to maintain a consistent slope of 0 to 0.2%. To move the soil either by cutting it or filling it in to create the proper slope or level, this procedure uses big horsepower about more than 55 hp tractors and soil movers outfitted with GPS and/or laser-guided instruments. In addition to lowering leveling cost, it ensures an appropriate level of precision. By removing pointless depressions and high contours, it enables efficient use of finite water resources. It has been noted that poor farm design and uneven field are responsible for 30% water losses.